Ceramics and the Spanish conquest: response and continuity of indigenous pottery technology in central Mexico - Hernández Sánchez, Gilda (The early Americas, 2012)
Archaeology of colonialism -- The study of material culture -- Ceramic-making before the conquest -- Ceramic-making in early colonial times -- Ceramic-making at present -- Ceramics, cultural continuity and social change